Task-specific reorganization of the auditory cortex in deaf humans - Łukasz Bola; Maria Zimmermann; Piotr Mostowski; Katarzyna Jednoróg; Artur Marchewka; Paweł Rutkowski; Marcin Szwed (2017)
The principles that guide large-scale cortical reorganization remain unclear. In the blind, several visual regions preserve their task specificity; ventral visual areas, for example, become engaged in auditory and tactile object-recognition tasks. It remains open whether task-specific reorganization is unique to the visual cortex or, alternatively, whether this kind of plasticity is a general principle applying to other cortical areas. Auditory areas can become recruited for visual and tactile input in the deaf. Although nonhuman data suggest that this reorganization might be task specific, human evidence has been lacking. Here we enrolled 15 deaf and 15 hearing adults into an functional MRI experiment during which they discriminated between temporally complex sequences of stimuli (rhythms). Both deaf and hearing subjects performed the task visually, in the central visual field. In addition, hearing subjects performed the same task in the auditory modality. We found that the visual task robustly activated the auditory cortex in deaf subjects, peaking in the posterior-lateral part of high-level auditory areas. This activation pattern was strikingly similar to the pattern found in hearing subjects performing the auditory version of the task. Although performing the visual task in deaf subjects induced an increase in functional connectivity between the auditory cortex and the dorsal visual cortex, no such effect was found in hearing subjects. We conclude that in deaf humans the high-level auditory cortex switches its input modality from sound to vision but preserves its task-specific activation pattern independent of input modality. Task-specific reorganization thus might be a general principle that guides cortical plasticity in the brain.